Improvement of Students and Snack Vendors Behavior After Received Health Promotion Program from UKS’s Cadres - Rina Doriana Pasaribu; Oslida Marthony; Sri Supriyantini; Dwi Nastiti Iswarawanti (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2022)
Background: School Health Program or UKS aims to improve  students learning achievement by improving their health status including the fulfillment of nutrition so that they can grow and develop optimally. The nutritional problems of school-age children in Indonesia, according to Riskesdas 2018 data, are children with the short/stunting category reaching 30.7%, while those who are obese are 8% and anemic 26%. Nutritional problems in school children will affect the quality of human resources in the future. Objectives: This study examined the effect of promoting healthy and safe snacks by UKS’s cadres on increasing knowledge, attitudes, behavior of students and snack sellers.Materials and Methods: The first stage of research was training elementary school students UKS’s cadres who will become educators on promoting healthy and safe food consumption behavior. The second stage was assessed to 360 randomly selected students and 94 school vendors in 12 different schools. The intervention schools received a package of promotions delivered by UKS’s cadres while the comparison group received the poster. Data on knowledge, attitudes, behavior of students and food sellers were collected using a questionnaire instrument. The data were collected by the researchers assisted by 12 enumerators, 6 research field assistants and 12 teachers in charge of the research field. Bivariate analysis using t-test, Wilcoxon test, and Mann Whitney test were used to assess the differences between the groups. Results: After intervention by UKS.s cadres, there was a change in students' knowledge of 51.1% for knowledge of healthy snacks, 52.8% about safe snacks, 82.8% about formalin, 62.8% about borax, and 75.6% about Rhodamine B. Changes in the behavior of snack sellers, the highest percentage of changes in holding food with tools is 62.5% and not holding food after holding money is 54.2%. Increased change were significantly higher in the intervention groups than the comparison group (p <0.05).Conclusion: The UKS’s cadres as trained peer-educators could significantly improve safe and healthy food behavior of students as well as knowledge of snack school vendors. UKS’s cadres as promoters of healthy and safe snacks can be used as a mandatory UKS program in school to achieve food safety for school children